Rare alpha-1-antitrypsin variants: are they really so rare? - Francisco Rodriguez-Frias; Marc Miravitlles; Rafael Vidal; Silvia Camos; Rosendo Jardi (Therapeutic Advances in Respiratory Disease, 2012)
Alpha-1-antitrypsin (α1-AT) deficiency is mainly evaluated in the diagnostic process of chronic obstructive pulmonary disease (COPD). Around 95% of individuals with severe α1-AT deficiency carry the PI*ZZ genotype. Little is known about the epidemiology of the remaining deficient α1-AT variants, which are called ‘rare’ due to their low prevalence. The retrospective revision of 3511 α1-AT deficiency determinations performed in Barcelona from 1998 to 2010 detected 1.6% of cases with rare α1-AT alleles, a rate similar to those reported in other European studies. Among these variants, PI*I and PI*Mmalton represented 54% of cases. Hence, the so-called ‘rare’ α1-AT alleles may not be rare as has been assumed. It would be of interest to implement simple allele-specific molecular biology methods to study the most prevalent rare variants in each region. Augmentation therapy is recommended in patients with emphysema and PI*ZZ genotype, but there is little evidence regarding the implications of rare variants on therapy.